2008
DOI: 10.1097/mcg.0b013e31802dbdfc
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Concurrent Autoimmune Disorders in Patients With Autoimmune Hepatitis

Abstract: The nature, but not the frequency, of CAID was shown to vary in AIH-1 and AIH-2. In subjects with AIH-1, CAID was linked to older subjects and to the presence of antinuclear antibody. No predisposition to CAID was associated to HLA-DRB1*04 or DDB4*01 alleles. The observed lower frequency of CAID could be attributed to the lower age of disease onset in Brazilians and to differences in HLA-encoded susceptibility to AIH-1 observed in South America.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
0
8

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 34 publications
6
54
0
8
Order By: Relevance
“…Concurrent extrahepatic autoimmune disorders (CAIDs) including autoimmune thyroiditis, diabetes, rheumatoid arthritis (RA) and ulcerative colitis (UC) are indeed common, ranging from approximately 20-49% of patients with AIH in various reports from different continents of the world [7][8][9][10][11][12][13][14][15][16][17][18][19] . Up to 43% of AIH patients report a family history of other autoimmune diseases in their first-degree relatives, commonly with thyroid disease and type 1 diabetes [9,15] .…”
Section: Frequency Of Concurrent Extrahepatic Diseasesmentioning
confidence: 99%
“…Concurrent extrahepatic autoimmune disorders (CAIDs) including autoimmune thyroiditis, diabetes, rheumatoid arthritis (RA) and ulcerative colitis (UC) are indeed common, ranging from approximately 20-49% of patients with AIH in various reports from different continents of the world [7][8][9][10][11][12][13][14][15][16][17][18][19] . Up to 43% of AIH patients report a family history of other autoimmune diseases in their first-degree relatives, commonly with thyroid disease and type 1 diabetes [9,15] .…”
Section: Frequency Of Concurrent Extrahepatic Diseasesmentioning
confidence: 99%
“…small duct PSC) [11]. Obserwuje się wówczas u chorych z AIH cechy zaostrzenia procesu zapalnego, którym towarzyszy uszkodzenie dróg żółciowych.…”
Section: Różnicowanie Zespołów Nakładania W Chorobach Wątrobyunclassified
“…However, shared HLAlinked susceptibility was reported to occur in AIH, PSC and AIHPSC overlap (24,177) . The impact of those overlapping features of more than one ALD in prognosis is not entirely clear, but lower response to treatment, accelerated disease progression, higher risk of treatment failure including death and requirement for Adapted from (2,7,9,10) ; AIH: autoimmune hepatitis; PBC: primary biliary cirrhosis; PSC: primary sclerosing cholangitis; ULN: upper limit of normal; ANA: antinuclear antibody; SMA: anti--smooth muscle antibody; AMA: antimitochondrial antibody; SMA: anti-smooth muscle antibody; AAA: antiactin antibody; ALP: alkaline phosphatase; AST: aspartatoaminotransferase; ALT: alaninoaminotransferase; MRCP: magnetic resonance cholangiopancreatography; ERC: endoscopic retrograde cholangiography LT were reported in subjects with AIH-PSC overlap, when compared to their counterparts with AIH (8,(175)(176)(177)(178) , but its prognosis was shown to be better when compared to pure PSC (176) . Regarding AIH-PBC overlap, several studies have shown lower response to ursodeoxicholic acid (UDCA), higher risk of disease progression and decompensation, when compared to classical PBC (139) .…”
Section: Part Iv: Overlap Syndromes Of Autoimmune Diseases Of the Livermentioning
confidence: 99%
“…The most frequent reported disorders were thyroiditis, either Hashimoto thyroiditis or Graves disease, and rheumatoid arthritis, but type 1 diabetes mellitus, Sjogren Syndrome, polymyositis, IgA deficiency, idiopathic thrombocytopenic purpura, urticaria, vitiligo, Addison's disease, inflammatory bowel diseases, celiac disease have also been associated with AIH. Sero-negative or rheumatoid arthritis and thyroiditis were the most frequent associated autoimmune diseases in Brazilian patients with AIH type I and AIH type II, respectively (1,2,10) .…”
Section: Brazilian Society Of Hepatology Recommendations For the Diagmentioning
confidence: 99%
See 1 more Smart Citation